Political Values, Culture, and Corporate Litigation - Hutton, Irena; Jiang, Danling; Kumar, Alok (Management Science, 2015)
Using one of the largest samples of litigation data available to date, we examine whether the political culture of a firm determines its propensity for corporate misconduct. We measure political culture using the political contributions of top managers, firm political action committees, and local residents. We show that firms with a Republican culture are more likely to be the subject of civil rights, labor, and environmental litigation than are Democratic firms, consistent with the Democratic ideology that emphasizes equal rights, labor rights, and environmental protection. However, firms with a Democratic culture are more likely to be the subject of litigation related to securities fraud and intellectual property rights violations than are Republican firms, whose party ideology stresses self-reliance, property rights, market discipline, and limited government regulation. Upon litigation filing, both types of firms experience similar announcement reaction, which suggests that the observed relationship between political culture and corporate misconduct is unlikely to reflect differences in expected litigation costs. Data, as supplemental material, are available at http://dx.doi.org/10.1287/mnsc.2014.2106 . This paper was accepted by Brad Barber, finance.